ТЭМЭЭН ЧУЛУУТЫН ОРДЫН ЗЭС (АЛТ)-НЫ ХҮДЭРЖИЛТ, ГАРАЛ ҮҮСЛИЙН АСУУДАЛД - O. Майбаяр; Л., Жаргал; Б., Дэлгэрцогт (Geological Issues, 2022)
Temeen Chuluut Copper Deposit is located in a (D1-2bd) quartz-sericite-chloritized schist thickness of Bayandun Formation of the Lower – Middle Devonian Period in Ulz and Bayandun Lowlands. For the purpose of researching the ore petrographic and the ore fluid inclusion of Temeen Chuluut Copper Deposit, 42 thin sections, 16 polished sections and 5 fluid inclusion samples were prepared and involved in the research. The deposit ore body is specifically located along the schist layering. The ore body and the containing rock metamorphosed into silicification, chloritization, epidotization, carbonization and sericitization. As a petrographic test, the ore body is composed of mineralized green schist parts which are similar with their mineral-containing composition of silicified and mineralized epidote–chlorite–quartzite schist, silicified and mineralized actinolite–epidote–chlorite–quartz-muscovitized schist, silicified and loosely mineralized-chlorite–epidote–albite–quartz-muscovitized schist, silicified, epidotized and mineralized muscotive–actinolite–chloritized schist and silicified, epidotized and mineralized chlorite–sericitized schist, but are different from each other in their mineral contents only. The ore has mineralized composition formed of some minerals such as muscovite, sericite, chlorite, epidote, albite, actinolite, carbonate, azurite, malachite, chalcopyrite, goethite, bornite, covellite, sphene, leucoxene, apatite, hydrogoethite and pyrite. The whitish-gray colored, semitransparent and mosaic textured quartz vein contains chalcopyrite, arsenopyrite and some other ore minerals. The quartz vein is metamorphosed into chloritization at its cleavage. And the ore minerals occur along with the metamorphosis. For the fluid inclusions occurring in the quartz of the samples involved in the research, vapor–liquid–clathrate phases-containing single to multi-phase fluid inclusions were found and there are a rich vapor component of H2О-NaCI-CO2 and a high temperature magmatogenic hydrothermal origin. The homogenizing temperature of the ore mineral-containing primary solution is 320 - 450 С degree. Its salinity is 20 - 37%.